Chirality Induction through Nano‐Phase Separation: Alternating Network Gyroid Phase by Thermotropic Self‐Assembly of X‐Shaped Bolapolyphiles. Issue 7 (7th January 2020) - Chen, Changlong; Kieffer, Robert; Ebert, Helgard; Prehm, Marko; Zhang, Rui‐bin; Zeng, Xiangbing; Liu, Feng; Ungar, Goran; Tschierske, Carsten
Abstract: The single gyroid phase as well as the alternating double network gyroid, composed of two alternating single gyroid networks, hold a significant place in ordered nanoscale morphologies for their potential applications as photonic crystals, metamaterials and templates for porous ceramics and metals. Here, we report the first alternating network cubic liquid crystals. They form through self‐assembly of X‐shaped polyphiles, where glycerol‐capped terphenyl rods lie on the gyroid surface while semiperfluorinated and aliphatic side‐chains fill their respective separate channel networks. This new self‐assembly mode can be considered as a two‐color symmetry‐broken double gyroid morphology, providing a tailored way to fabricate novel chiral structures with sub‐10 nm periodicities using achiral compounds. Abstract : Self‐sorting of the two poorly compatible side‐chains of X‐shaped polyphiles into their own networks gives rise to a chiral gyroid cubic phase (the "single gyroid" I 41 32) with two chemically non‐equal networks. This is the first alternating network gyroid cubic liquid crystal, and the first liquid crystal with chirality solely based on phase separation, allowing the self‐assembly of chiral structures with sub‐10 nm periodicities.